2023
DOI: 10.1002/jad.12218
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between loneliness and problematic smartphone use among adolescents during the COVID‐19 pandemic: The mediating role of negative emotions and maladaptive coping

Abstract: IntroductionGiven the observed increased feelings of loneliness and problematic smartphone use among adolescents during the COVID‐19 pandemic, further research was needed to determine whether and how the increased loneliness of adolescents during such major public health crisis events affects the risk of problematic smartphone use among adolescents. This study aimed to examine the relationship between loneliness and problematic smartphone use among Chinese adolescents (aged 10–16 years) during the COVID‐19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…The participants in current study exhibited a higher level of PMPU compared to a previous study conducted in Heilongjiang Province, China (mean of the sum score: 5.13 ± 1.53) [ 42 ]. In addition to the influence of COVID-19 [ 9 ], geographic factors may affect students’ PMPU. For instance, adults in municipalities reported a longer duration of mobile phone use in a previous study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants in current study exhibited a higher level of PMPU compared to a previous study conducted in Heilongjiang Province, China (mean of the sum score: 5.13 ± 1.53) [ 42 ]. In addition to the influence of COVID-19 [ 9 ], geographic factors may affect students’ PMPU. For instance, adults in municipalities reported a longer duration of mobile phone use in a previous study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale study found that the prevalence of problematic mobile phone use was as high as 27.5% among Chinese college students [ 8 ]. Due to the heightened loneliness resulting from home quarantine and increased negative emotions during the COVID-19 pandemic, smartphone addiction has become a prominent issue among students in mainland China [ 9 ]. Extensive research substantiates that PMPU adversely affects individuals, leading to issues such as the difficulty concentrating, an increased risk of suicide, and depression [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%